Preparation, characterization and catalytic application of nano-Fe3O4-DOPA-SnO2 having high TON and TOF for non-toxic and sustainable synthesis of dihydroquinazolinone derivatives. (20th June 2017) - Dam, Binoyargha; Patil, Ranjit A.; Ma, Yuan-Ron; Pal, Amarta Kumar
Abstract : A novel class of heterogeneous magnetically separable nano catalysts was designed by encapsulating SnO2 on nano-Fe3 O4 -DOPA. And is applied for the synthesis of dihydroquinazolinone derivatives. Abstract : A novel class of heterogeneous magnetically separable nano catalysts was designed by encapsulating SnO2 on nano-Fe3 O4 -DOPA. After the successful characterization of the synthesized catalyst by FT-IR, SEM, TEM, EDX, TGA, powder XRD, XPS, VSM and ICP-AES, it was employed in the greener synthesis of dihydroquinazolinone derivatives using water as a solvent. Nano-Fe3 O4 -DOPA-SnO2 was found to have high TON and TOF and showed high catalytic activity which is validated by good to excellent yields of the desired products. The application of the present protocol was also carried out for the synthesis of bis-dihydroquinazolinone compounds which leads to the formation of six new C–N bonds, two new C–C bonds, two new stereocentres and two new dihydroquinazolinone moieties in one step within a shorter period of time. Easy separation and reusability of the catalyst (five times), substrate variation, selectivity of desired products, shorter reaction time, greener reaction medium (water), column chromatography free separation, gram scale reaction and easy workup procedures rendered this procedure environmentally friendly and sustainable. Furthermore, biologically important quinazolinones were synthesized from dihydroquinazolinone derivatives by a simple oxidation technique.